Genome-wide identification and expression analysis of the growth regulating factor (GRF) family in Jatropha curcas. - Yuehui Tang (Public Library of Science (PLoS), 2021)
GRF genes have been confirmed to have important regulatory functions in plant growth, development and response to abiotic stress. Although the genome of Jatropha curcas is sequenced, knowledge about the identification of the species' GRF genes and their expression patterns is still lacking. In this study, we characterized the 10 JcGRF genes. A detailed investigation into the physic nut GRF gene family is performed, including analysis of the exon-intron structure, conserved domains, conserved motifs, phylogeny, chromosomal locations, potential small RNA targets and expression profiles under both normal growth and abiotic stress conditions. Phylogenetic analysis indicated that the 10 JcGRF genes were classified into five groups corresponding to group I, II, III, IV and V. The analysis of conserved domains showed that the motifs of JcGRF genes were highly conserved in Jatropha curcas. Expression analysis based on RNA-seq and qRT-PCR showed that almost all JcGRF genes had the highest expression in seeds, but very low expression was detected in the non-seed tissues tested, and four JcGRF genes responded to at least one abiotic stress at at least one treatment point. Our research will provide an important scientific basis for further research on the potential functions of JcGRF genes in Jatropha curcas growth and development, and response to abiotic stress, and will eventually provide candidate genes for the breeding of Jatropha curcas.